The Effect of Work Environment, Workload, and Work Engagement on Employee Performance with Work Commitment as mediation and Generation Z as Control Variable in Batam City - Muhammad Donal Mon; Jane Evelin Susilo; Antony Sentoso (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This research aims to determine the influence of work environment, workload, and work engagement on employee performance with work commitment as a mediation for generation Z. This research uses descriptive quantitative methods and 400 respondents, with generation Z as the population. SMART PLS were used as the data processing technique. The results of the analysis from this research shows that environment, workload, and work engagement have a significant positive influence on performance with work commitment as a mediation for generation Z in Batam. The usage of gender as control variables in this research is unique/different and the result shows that gender does not have a significant influence on the performance of generation Z.